Relationship Play Online Games With Motivation Learning In Teens - Nurhalisa; Aszrul AB; Nurlina (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2021)
The use of uncontrolled games in adolescents can affect the learning process in school, especially the interest or desire to learn teenagers become reduced or can even disappear, this can certainly interfere with the child's education in the future. The decrease in students' desire to learn seriously can be influenced by the motivation of the student itself, namely the motivation of the student. The purpose of this study is to find out the relationship of playing online games with learning motivation in the youth of SMPN 41 Bulukumba students. This study uses an analytical observational research design with a